A perception among Malays people towards insurances / Mohd Harithan Ahmad Tarmizi - Ahmad Tarmizi, Mohd Harithan (Faculty of Business and Management, 2010)
As an insurance company, customers are the most importance key in theEtiqa Takaful Bhd as the business nature. The satisfaction of the customer will ensure the business growth and the strengths to compete with other rivals in the market. Based on this believe, this study was conducted which is to know whether Etiqa Takaful Bhd is fulfilling the customer needs in their life. For the Chapter 1 explaining the background of study, Chapter 2 explains the literature review and theoretical framework, Chapter 3 focus to research methodology and Chapter 4 will followed by finding and lastly conclusion and recommendation. The finding shows the factors that contribute to the perception among Malay people towards insurance and insurance company need to take an action to overcome the problems.